Research on the Optimization of Operating Parameters of Steam Injection Pipe Network - Liu, Junfeng (International Journal of Electric Power and Energy Studies, 2024)
Scientifically optimizing the design of the steam injection pipe network is an important way to improve economic benefits, enhance oil production efficiency, and reduce energy consumption. In the study of the optimal layout of the steam injection pipe network, the operating parameters and operation schemes of the oilfield steam injection system were optimized, and a mathematical model of wet steam flow in dendritic pipelines was established. The genetic algorithm code was written in MATLAB for optimization, and the results were compared with the current steam network layout. The reliability has been proven and can be used as a reference for future pipe network layout studies. Taking the minimum energy consumption loss in the steam injection process as the objective function, an appropriate genetic optimization algorithm was selected to solve the mathematical model for three well parameters. Corresponding constraints and optimization principles were established with the main purpose of reducing energy consumption and improving efficiency. The relevant steam injection parameters were optimized and calculated, and the site of the steam injection station was determined.